DOES NOVELTY-SEEKING DRIVE PURCHASE DECISIONS? UNDERSTANDING CONSUMER DESIRES TO BUY COUNTERFEIT PRODUCTS - Wijaya, Angga Pandu; Prihandono, Dorojatun; Wiratama, Bayu; Rawi, Fauziana Fauzi @ Mat (Faculty of Economic and Business, University of Pasundan, 2023)
This study aims to analyze the effect of product knowledge and product appearance on counterfeit product purchasing decisions through novelty seeking. In the current era, consumers use many counterfeit products as an alternative to the original product. The research using quantitative study by testing 148 samples as users of counterfeit products. The results showed product knowledge and product appearance positively impact on purchasing decisions. In addition, the appearance that imitates the original product tends to be liked because of its innovation. Research also proves that novelty seeking strengthens the effect of product knowledge and product appearance on purchasing decisions. The determinants of counterfeit product purchase, including product knowledge and product appearance, have limited understanding. The research indicates that when consumers have adequate knowledge of the product, they have identical desire to buy counterfeit product as the original product because it has a novelty. Research limitation only focuses on fashion counterfeit product (clothes and shoes), further study should expand in another types of product to gain comprehensive understanding.